Радиационные дефекты в пиролитическом нитриде бора - Кабышев А. В. Александр Васильевич; Кецкало В. М.; Лопатин В. В. Владимир Васильевич; Сериков Л. В.; Суров Ю. П.; Шиян Л. Н. Людмила Николаевна (1990, 1990)
В фонде НТБ ТПУ отсутствует